2020
DOI: 10.1002/cncr.33257
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported physical activity, sitting time, and mental and physical health among older cancer survivors compared with adults without a history of cancer

Abstract: BACKGROUND: To the authors' knowledge, few studies to date have examined associations between moderate to vigorous physical activity (MVPA) and sitting time with quality of life in cancer survivors compared with a cancer-free group. The current study examined differences in global mental health (GMH) and global physical health (GPH) across levels of MVPA and sitting among cancer survivors and cancer-free participants. METHODS: Cancer Prevention Study II participants (59.9% of whom were female with an age of 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Because newly diagnosed cancer survivors are more likely to be receiving curative or palliative care that may acutely affect fracture risk, survival, and other variables examined, the first year after the date of diagnosis was excluded from the main analysis but was included in an analysis examining risk by single year since diagnosis. These analytic decisions align with those made in previous studies of bone health in cancer survivors and with other studies of cancer survivorship within CPS-II NC …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because newly diagnosed cancer survivors are more likely to be receiving curative or palliative care that may acutely affect fracture risk, survival, and other variables examined, the first year after the date of diagnosis was excluded from the main analysis but was included in an analysis examining risk by single year since diagnosis. These analytic decisions align with those made in previous studies of bone health in cancer survivors and with other studies of cancer survivorship within CPS-II NC …”
Section: Methodsmentioning
confidence: 99%
“…These analytic decisions align with those made in previous studies of bone health in cancer survivors 11 and with other studies of cancer survivorship within CPS-II NC. 23…”
Section: Study Populationmentioning
confidence: 99%
“…While this relationship is undoubtedly multifactorial, increasing physical activity and decreasing sedentary lifestyle habits have been shown to be associated with improved mental and physical health as people age. 1,2,31 Despite the overall high patient satisfaction with surgical outcomes and return to prior activities in the present study, there were 10 patients (16%) who reported satisfaction scores \7; of 4 (6.4% of entire cohort) of whom were deemed to have ''poor'' outcomes because of corresponding ASES scores of \75. Interestingly, each patient reported moderate (3) or severe (1) pain with recreation and mild (2) or moderate (2) pain with sleep, indicating that pain resolution is likely a central focus of this patient cohort.…”
Section: Discussionmentioning
confidence: 54%
“…While this relationship is undoubtedly multifactorial, increasing physical activity and decreasing sedentary lifestyle habits have been shown to be associated with improved mental and physical health as people age. 1,2,31…”
Section: Discussionmentioning
confidence: 99%
“…During this phase, the adoption of healthy lifestyle habits is crucial to countering these effects. However, to date, the concurrent associations of PA and ST with psychological functioning and QoL during this period remain poorly understood in adults with cancer [25]. Indeed, while a few reviews have investigated the associations between PA and psychosocial functioning in this population (e.g., [26,27]), ST is a much more recent concept that is often misinterpreted as physical inactivity rather than a distinct behaviour with unique health implications.…”
Section: Introductionmentioning
confidence: 99%